Secondary battery and electronic device

By using an electrolyte containing sulfur additives in lithium-ion batteries, and controlling the morphological characteristics of the positive electrode active material and the sulfur content of the negative electrode sheet, the problem of low capacity retention rate and insufficient high-temperature self-discharge performance under high and low temperature interval cycles is solved, and better cycle stability and self-discharge performance are achieved.

CN119812468APending Publication Date: 2025-04-11CHINA AVIATION LITHIUM BATTERY LUOYANG
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411919836.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The existing lithium-ion batteries have low capacity retention under high and low temperature interval cycling conditions, and the self-discharge performance at high temperatures is insufficient, which affects the battery's cycle life and storage life.

Method used

By using an electrolyte containing sulfur additive in the secondary battery, and controlling the aspect ratio and particle size change ratio of the primary particles of the positive electrode active material in the positive electrode sheet, combined with the mass content of sulfur elements in the negative electrode sheet, a specific relationship is met to improve the high and low temperature cycle performance and self-discharge performance of the battery.

Benefits of technology

High capacity retention rate under high and low temperature interval cycling conditions is achieved, and the self-discharge performance at high temperatures is significantly improved, which extends the storage life of the battery and reduces energy loss.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005207688420000151
    Figure BDA0005207688420000151
  • Figure BDA0005207688420000161
    Figure BDA0005207688420000161
  • Figure BDA0005207688420000191
    Figure BDA0005207688420000191
Patent Text Reader

Abstract

The invention discloses a secondary battery and an electronic device, and belongs to the technical field of electrochemistry. The secondary battery comprises a positive pole piece, a negative pole piece and an electrolyte, the secondary battery satisfies the following relational expressions: a = (H50) 2-(1 / 3) H50 + D50, b = MS, 7.3 < = a * Ln (b) < = 14.8; wherein H50 is the corresponding length-diameter ratio when the cumulative distribution percentage of the number of primary particles of the positive electrode active material reaches 50%; d50 is a DV50 particle size change ratio before and after the positive electrode active material is subjected to pressure maintaining for 30s under the pressure of 35KN; mS is the mass content of the sulfur element in the negative pole piece. By comprehensively controlling the length-diameter ratio and the particle size change rate of the positive electrode active material and the content of the sulfur element in the negative electrode plate, the secondary battery has a relatively high capacity retention ratio under a high-low temperature interval cycle condition, and the self-discharge performance at a high temperature is remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of electrochemical technology, and in particular to a secondary battery and an electronic device. Background Art

[0002] In today's society, lithium-ion batteries, as a high-performance, high-energy-density energy storage device, have been widely used in mobile communications, electric vehicles, wearable devices and other fields.

[0003] Under high temperature environment, the working performance of the battery often faces more severe tests. Improving the high temperature cycle performance of the battery is an important direction of current research. At present, through different technical means, such as modification of active materials and optimization of electrolytes, significant progress has been made in the high temperature cycle performance of lithium-ion batteries.

[0004] In actual use, batteries often need to work in different temperature ranges, and temperature changes may have an adverse effect on the battery's cycle life and performance stability. Batteries still face challenges in high and low temperature interval cycle performance.

[0005] In addition, the self-discharge problem of secondary batteries in actual use also needs to be better solved. In secondary batteries, especially lithium-ion secondary batteries, the interfacial oxidation activity between the pole piece and the solvent is very high during charging and storage. When the solvent contacts the positive electrode interface, an oxidation decomposition reaction will occur, resulting in an unstable positive electrode material structure, reduced ability and speed of lithium insertion and extraction, and further leading to continuous self-discharge inside the secondary battery cell and accelerated secondary battery life decay. Self-discharge is one of the important indicators of battery performance and is directly related to the battery life and efficiency. At present, the self-discharge performance of the battery needs to be further improved to extend the storage life of the battery and reduce energy loss.

[0006] Therefore, it is necessary to provide a secondary battery with good high and low temperature cycle performance and improved self-discharge. Summary of the invention

[0007] The object of the present invention is to overcome the shortcomings of the prior art and provide a secondary battery and an electronic device, wherein the secondary battery has a higher capacity retention rate under high and low temperature interval cycle conditions and has significantly improved self-discharge performance at high temperatures.

[0008] To achieve the above object, in a first aspect of the present invention, the present invention provides a secondary battery, comprising: a positive electrode sheet, a negative electrode sheet and an electrolyte; the positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, the positive electrode active material layer comprising a positive electrode active material;

[0009] The electrolyte includes a sulfur-containing additive;

[0010] The secondary battery satisfies the following relationship:

[0011] a=(H 50 ) 2 -(1 / 3)H 50 +△D 50 , b=M S , 7.3≤a×Ln(b)≤14.8;

[0012] Among them, H 50 The aspect ratio corresponding to the cumulative distribution percentage of the primary particles of the positive electrode active material reaching 50%;

[0013] △D 50 D is the positive electrode active material under 35KN pressure for 30s before and after V 50 particle size change ratio;

[0014] M S It is the mass content of sulfur element in the negative electrode plate, in ppm.

[0015] As a preferred embodiment of the present invention, the secondary battery satisfies the following relationship: 8.8≤a×Ln(b)≤13.3.

[0016] As a preferred embodiment of the present invention, the sulfur-containing additive includes at least one of a sulfonate additive, a sulfate additive or a sulfite additive.

[0017] As a preferred embodiment of the present invention, the sulfonate additive includes at least one of methylene methanedisulfonate, ethylene ethanedisulfonate, propylene methanedisulfonate, 1,3-propane sultone, 1-propylene-1,3-sultone or 1,4-butane sultone.

[0018] As a preferred embodiment of the present invention, the sulfate ester additive includes at least one of vinyl sulfate, 4-methylethylene sulfate, 4-ethylethylene sulfate, 4-propylethylene sulfate or propylene sulfate.

[0019] As a preferred embodiment of the present invention, the sulfite additive includes at least one of vinyl sulfite, dimethyl sulfite or diethyl sulfite.

[0020] As a preferred embodiment of the present invention, the H 50 The range is 1.2 to 1.6.

[0021] As a more preferred embodiment of the present invention, the H 50 The range is 1.32~1.53.

[0022] As a preferred embodiment of the present invention, the ΔD 50 The range is 0.60~0.90.

[0023] As a more preferred embodiment of the present invention, the ΔD 50 The range is 0.60~0.82.

[0024] As a preferred embodiment of the present invention, the M S The range is 70~200ppm.

[0025] As a more preferred embodiment of the present invention, the M S The range is 80~180ppm.

[0026] As a preferred embodiment of the present invention, the positive electrode active material comprises a ternary positive electrode material, the chemical formula of which is LiNi x Co y Mn (1-x-y) O2, where 0.7≤x<1, 0<y≤0.3, 0<x+y<1.

[0027] In a second aspect of the present invention, the present invention provides an electronic device comprising the secondary battery described above.

[0028] The beneficial effects of the present invention are:

[0029] The present invention provides a secondary battery and an electronic device. The electrolyte in the secondary battery of the present invention includes a sulfur-containing additive, and by comprehensively controlling the aspect ratio of primary particles of positive electrode active materials in the positive electrode plate, the particle size change rate of the positive electrode active materials, and the sulfur content in the negative electrode plate, the secondary battery of the present invention has a higher capacity retention rate under high and low temperature interval cycle conditions, and the self-discharge performance at high temperature is significantly improved. DETAILED DESCRIPTION

[0030] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] In the present invention, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0032] In the present invention, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values ​​of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0033] In the present invention, there is no particular limitation on the specific dispersion and stirring treatment methods.

[0034] The reagents or instruments used in the present invention without indicating the manufacturer are all conventional products that can be obtained through commercial purchase.

[0035] Secondary battery

[0036] An embodiment of the present invention provides a secondary battery, comprising: a positive electrode plate, a negative electrode plate and an electrolyte; the positive electrode plate comprises a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, the positive electrode active material layer comprising a positive electrode active material;

[0037] The electrolyte includes a sulfur-containing additive;

[0038] The secondary battery satisfies the following relationship:

[0039] a=(H 50 ) 2 -(1 / 3)H 50 +△D 50 , b=M S , 7.3≤a×Ln(b)≤14.8;

[0040] Among them, H 50 The aspect ratio corresponding to the cumulative distribution percentage of the primary particles of the positive electrode active material reaching 50%;

[0041] △D 50 D is the positive electrode active material under 35KN pressure for 30s before and after V 50 particle size change ratio;

[0042] M S It is the mass content of sulfur element in the negative electrode plate, in ppm.

[0043] In the present invention, an electrolyte containing a sulfur-containing additive is used to control the aspect ratio of the primary particles of the positive electrode active material and the particle size change ratio of the positive electrode active material under pressure. Combined with the content of sulfur in the negative electrode plate, the parameters are comprehensively adjusted to satisfy the above relationship, so that the secondary battery has excellent high and low temperature cycle performance and the self-discharge situation is also significantly improved.

[0044] For positive electrode active materials, they generally include primary particles and / or secondary particles, where "primary particles" refer to the primary structure of a single particle, i.e., single crystal particles; "secondary particles" refer to an aggregate in which primary particles are aggregated through physical or chemical bonding between primary particles, i.e., a secondary structure.

[0045] The aspect ratio (H) corresponding to the cumulative distribution percentage of the primary particles of the positive electrode active material reaching 50% 50 ) refers to the ratio of the major axis length to the minor axis length of the single-crystal positive electrode active material particles when the cumulative distribution percentage reaches 50%.

[0046] H 50 The size of reflects the morphological characteristics of the primary particles of the positive electrode active material. 50 Under this condition, the positive electrode active material can provide better structural density for the positive electrode active material layer, reduce defects and unstable areas on the surface of the positive electrode active material layer, thereby reducing the locations that may cause self-discharge of the secondary battery, and also help the secondary battery to have better cycle stability under different conditions.

[0047] This study found that due to the volume change of the positive electrode active material during the charge and discharge cycle of the secondary battery, H 50 When H is too large, the volume changes of different parts inside the positive electrode active material may be uneven. This uneven volume change will cause stress concentration inside the particles. Due to the difference between the major axis length and the minor axis length, there may be differences in mechanical properties inside the particles of the positive electrode active material, such as elastic modulus, hardness, etc.; when H 50 When it is too large, the difference in these mechanical properties may be too large, which will lead to uneven distribution of stress inside the particles and reduce the particle strength of the positive electrode active material. 50 Oversized positive electrode active materials have too many exposed active sites and too large a contact area between the active sites and the electrolyte. Under high temperature placement or harsh cycle conditions of high and low temperature cycles, the mechanical property differences within the positive electrode active materials will be magnified, and the risk of stress concentration will increase, resulting in decreased battery cycle stability, excessive side reactions between the positive electrode active materials and the electrolyte, and deterioration of self-discharge.

[0048] In the present invention, the particle size change ratio (ΔD 50) D of the positive electrode active material before and after holding the pressure at 35KN for 30s V The particle size change of the positive electrode active material is calculated. The particle size change of the positive electrode active material is related to the particle strength of the positive electrode active material and the proportion of secondary particles. As the positive electrode active material is subjected to pressure, the secondary particles of the positive electrode active material may break into multiple particles with smaller particle sizes, or the primary particles and / or secondary particles may be deformed or broken to a certain extent.

[0049] For the secondary battery of the present invention, the positive electrode active material has a suitable ΔD 50 It helps to improve the cycle stability and self-discharge performance of the battery.

[0050] Secondary particles are aggregates that are aggregated by physical or chemical bonding between primary particles. In the present invention, primary particles with a certain aspect ratio are aggregated into secondary particles, which can alleviate the stress concentration caused by the uneven expansion and contraction of the particle volume during the battery charging and discharging process in the positive electrode active material, thereby improving the performance stability of the battery. In addition, for positive electrode active materials, a certain particle size change ratio often means that there are pores and voids inside the positive electrode active material layer, and these pores and voids may be generated by the rolling step during the preparation of the positive electrode sheet. During the charging and discharging process of lithium-ion batteries, the positive electrode active material will experience volume expansion and contraction. A higher particle size change ratio can provide more space to accommodate volume changes, thereby reducing the risk of stress concentration and damage, and thereby improving the capacity retention rate of the positive electrode sheet after high and low temperature cycles.

[0051] However, this study found that △D 50 It should not be too high. As mentioned above, △D 50 In addition to being affected by the proportion of secondary particles, it is also related to the particle strength of the positive electrode active material. 50 When it is relatively high, it means that the particle strength of the positive electrode active material is relatively low. The positive electrode active material requires appropriate particle strength to ensure that the material has good structural strength and stability. If the particle strength is too low, it may cause the stability of the positive electrode active material layer to deteriorate, causing the cycle performance of the battery containing the positive electrode sheet to deteriorate. In addition, when the particle strength of the positive electrode active material is low, there may be more microscopic cracks, gaps or holes inside the positive electrode active material particles, which will cause more active sites to contact the electrolyte, increasing the risk of battery self-discharge.

[0052] Considering the H 50 It will also affect △D 50 The size of H 50 The increase of △D 50 It may increase first and then decrease), in the present invention, H 50 and △D50 Comprehensively reflects the morphology and structural characteristics of the positive electrode active material. 50 and △D 50 The relationship is a nonlinear relationship. The present invention uses a=(H50)2-(1 / 3)H50+△D50 to comprehensively fit the morphology and structural characteristics of the positive electrode active material.

[0053] For the electrolyte in the secondary battery, the present invention adopts an electrolyte including a sulfur-containing additive. The sulfur element in the negative electrode plate mainly comes from the sulfur in the sulfur-containing additive in the electrolyte. During the charge and discharge process of the battery, the components in the electrolyte (including the lithium ions, solvents, etc.) form a passivation layer on the surface of the negative electrode plate, namely the SEI film (solid electrolyte interface film located on the surface of the negative electrode). In this process, the sulfur element in the sulfur-containing additive is introduced into the negative electrode plate. During the cycle or static use of the battery, the electrolyte will continue to react at the negative electrode interface to generate specific reaction products. The sulfur-containing additive used in the present invention is mainly used for reactions on the surface of the negative electrode.

[0054] A certain amount of sulfur-containing additives in the electrolyte can improve the composition and structure of the solid electrolyte interface film, prevent the redox decomposition of non-aqueous organic solvents on the surface of the pole piece, stabilize the interface between the electrolyte and the electrode, thereby improving the cycle stability of the battery, reducing the rate of self-discharge, and improving the self-discharge of the battery. However, since sulfur is a poor conductor of lithium ions and electrons, a high content of sulfur will lead to an increase in battery impedance, increase battery polarization, and accelerate the capacity decay of the battery during the cycle.

[0055] Although the electrolyte can also form a CEI film (solid electrolyte interface film located on the surface of the positive electrode) on the surface of the positive electrode of the battery, this study found that S has no significant effect on the positive electrode CEI film.

[0056] This study found that by comprehensively controlling the H content of the positive electrode active material in the positive electrode sheet of the secondary battery 50 and △D 50 , and M in the negative electrode S , so that it satisfies the relationship: a=(H 50 ) 2 -(1 / 3)H 50 +△D 50 , b=M S , 7.3≤a×Ln(b)≤14.8, the secondary battery has excellent high and low temperature cycle performance, and the self-discharge at high temperature is also significantly improved.

[0057] Illustratively, in the present invention, the value of a×Ln(b) may be 7.3, 7.5, 7.8, 8.0, 8.5, 9.0, 10.0, 12.0, 13.0, 13.5, 14.0, 14.5, or 14.8, or may be an interval formed by any two of the above values.

[0058] In one embodiment, the secondary battery satisfies the following relationship: 8.8≤a×Ln(b)≤13.3.

[0059] When the value of a×Ln(b) further satisfies 8.8~13.3, the relevant parameters of the positive electrode plate, negative electrode plate and electrolyte in the secondary battery are better coordinated, and the high and low temperature cycle performance and self-discharge of the battery are greatly improved.

[0060] In one embodiment, the H 50 The range is 1.2 to 1.6. For example, the H 50 It can be 1.20, 1.22, 1.25, 1.28, 1.30, 1.35, 1.40, 1.45, 1.50, 1.53, 1.55, 1.58, and 1.60.

[0061] In a more preferred embodiment, the H 50 The range is 1.32~1.53.

[0062] In the above H 50 Within the range of , the primary particles of the positive electrode active material have a suitable aspect ratio, which can not only provide better structural density for the positive electrode sheet, reduce defects and unstable areas on the surface of the positive electrode active material layer, but also avoid the risk of excessive stress concentration, excessive difference in mechanical properties or excessive side reactions with the electrolyte.

[0063] For H 50 The present invention does not limit the determination method, and those skilled in the art can use conventional technical means to determine. For example, SEM testing can be used to obtain the H of the positive electrode active material. 50 .

[0064] Exemplarily, H can be performed as follows 50 Determination of:

[0065] The lithium-ion battery is disassembled to obtain a positive electrode sheet, and the positive electrode sheet is soaked in DMC (dimethyl carbonate) at room temperature for 60 minutes, taken out, and air-dried at room temperature with a humidity of ≤15%; the positive electrode active material layer on the surface of the current collector is scraped off, and calcined at 450° C. for 3 hours to remove the conductive agent, binder, surface side reaction products, and residual electrolyte, and the positive electrode active material is obtained after washing and drying;

[0066] The positive electrode active material (3 g) was placed in a clean agate mortar, manually ground with a pestle for 5 min, passed through a 100-mesh sieve, and subjected to SEM testing; the nano measurer software was used to observe the 2.5K magnification particle morphology and measure the ratio of the major axis length to the minor axis length of the primary particles of the positive electrode active material; the number of samples collected was 200, and the aspect ratio corresponding to the cumulative distribution percentage of 50% was H. 50 .

[0067] The aspect ratio of the cathode active material is related to many factors. It can be adjusted by selecting cathode active material precursors with different morphologies, changing the preparation conditions of cathode active material precursors, and adjusting the sintering and grinding process parameters after the cathode active material precursors and lithium source are mixed. 50 Control; positive electrode active materials with specific aspect ratios can also be obtained through large-scale screening.

[0068] In one embodiment, the ΔD 50 The range is 0.50 to 0.90. For example, the △D 50 It can be 0.50, 0.55, 0.60, 0.65, 0.68, 0.70, 0.75, 0.80, 0.82, 0.85, 0.88, and 0.90.

[0069] In one of the more preferred embodiments, the ΔD 50 The range is 0.60~0.82.

[0070] Within the above-mentioned range of particle size change ratio, the positive electrode active material has suitable particle strength and secondary particle ratio, which can not only ensure that the positive electrode plate has good structural strength and stability, but also enable the positive electrode plate to have suitable pores and gaps, which can alleviate the stress concentration caused by the uneven expansion and contraction of the volume of the positive electrode active material, improve the performance stability of the battery, and reduce the risk of battery self-discharge.

[0071] About △D 50 The present invention does not limit the detection method, and those skilled in the art can detect the particle size change ratio of the positive electrode active material according to conventional technical means. For example, ΔD 50 The following methods can be used for detection:

[0072] The lithium-ion battery is disassembled to obtain a positive electrode sheet, and the positive electrode sheet is soaked in DMC (dimethyl carbonate) at room temperature for 60 minutes, taken out, and dried at room temperature with a humidity of ≤15%; the positive electrode active material layer on the surface of the current collector is scraped off, and calcined at 450° C. for 3 hours to remove the conductive agent, the binder, the surface side reaction products, and the residual electrolyte, and the positive electrode active material is obtained through post-treatment;

[0073] The positive electrode active material was dispersed in an aqueous solution containing 3% sodium hexametaphosphate dispersant, and after continuous stirring with a glass rod for 10 circles, all the samples were quickly poured into the particle size distribution instrument test sample pool for D V 50 tests, get D before pressure maintenance V 50, denoted as D V 50 压前 ;

[0074] Then, the mixture containing the positive electrode active material is subjected to solid-liquid separation and drying to obtain the positive electrode active material again, and the positive electrode active material is pressed at a pressure of 35KN for 30s using a powder compactor; after the pressure is maintained, the positive electrode active material is taken out and D is measured again using a particle size tester according to the above method. V 50 test, get D after pressure maintenance V 50, denoted as D V 50 压后 ;

[0075] The particle size change ratio (△D 50 ):

[0076] △D 50 =|(D V 50 压前 -D V 50 压后 )| / D V 50 压前 ;

[0077] Among them, D V 50 is the particle size corresponding to when the cumulative volume distribution percentage of the positive electrode active material reaches 50%, in μm.

[0078] The particle size variation ratio of the positive electrode active material is related to many factors and can be controlled by changing the precursor of the positive electrode active material, the pulverization conditions during the preparation process, and the heat treatment conditions; the positive electrode active material with a specific particle size variation ratio can also be obtained through large-scale screening.

[0079] As a preferred embodiment of the present invention, the M S The range is 70 to 200 ppm. For example, the M S It can be 70ppm, 75ppm, 80ppm, 90ppm, 100ppm, 120ppm, 150ppm, 180ppm, 190ppm, 195ppm, 200ppm.

[0080] As a more preferred embodiment of the present invention, the M S The range is 80~180ppm.

[0081] M SWhen the above preferred range is met, the SEI film of the negative electrode plate of the secondary battery has good structural stability, the self-discharge performance of the battery is improved, and the cycle stability is better.

[0082] About M S The present invention does not limit the detection method, and those skilled in the art can detect the sulfur content in the negative electrode sheet according to conventional technical means. S The following methods can be used for detection:

[0083] Disassemble the lithium-ion battery to obtain the negative electrode sheet, soak the negative electrode sheet in DMC (dimethyl carbonate) at room temperature for 12 hours, take it out, replace it with new DMC and soak the negative electrode sheet again for cleaning, and repeat the cleaning several times until the sulfur content detected in the DMC solution is less than 5ppm;

[0084] The cleaned negative electrode sheet was taken out and ICP test was performed. The specific test conditions were as follows: scrape off the negative electrode active material layer on the surface of the negative electrode current collector, weigh 0.5g of the sample and dissolve it in 20ml of water, then add 10ml of nitric acid, heat to dissolve, dilute with water, and finally filter to obtain the test solution; pipette 10ml of the test solution and continue to add 5ml of hydrochloric acid and continue to dilute with water to 100ml; the obtained solution was calibrated and tested with iCAP PRO XP inductively coupled plasma emission spectrometer, according to the standard curve method, horizontal observation angle, constant temperature 25°C; M S .

[0085] M S The value of is related to the type and content of sulfur-containing additives in the electrolyte, and also to the electrochemical reaction of the battery. Since the electrochemical reaction involves the flow of ions and electrons between the positive and negative electrodes, the type of positive electrode active material and different interface designs (such as ternary positive electrode materials with different Ni contents, doping or coating of metal W elements, etc.) will trigger different types and degrees of interfacial side reactions, thereby changing the electrolyte components, and even some elements will be deposited on the surface of the negative electrode, affecting the reaction between the negative electrode and the electrolyte, resulting in changes in the Ms value.

[0086] As a preferred embodiment of the present invention, the positive electrode active material comprises a ternary positive electrode material, the chemical formula of which is LiNi x Co y Mn (1-x-y) O2, where 0.7≤x<1, 0<y≤0.3, 0<x+y<1.

[0087] In the present invention, for LiNi x Co y Mn (1-x-y)The preparation method of O2 is not limited, and those skilled in the art can prepare the positive electrode active material according to conventional technical means. Exemplarily, the positive electrode active material precursor and the lithium source are mixed and sintered to obtain the positive electrode active material.

[0088] The positive electrode active material precursor may be one or more of oxides, hydroxides and carbonates containing Ni, Co and Mn in a stoichiometric ratio, for example, a hydroxide containing Ni, Co and Mn in a stoichiometric ratio. The positive electrode active material precursor may be obtained by methods known in the art, for example, by coprecipitation, gelation or solid phase method.

[0089] As an example, the preparation method of the positive electrode active material precursor may include the following steps:

[0090] A Ni source, a Co source and a Mn source are dispersed in a solvent to obtain a mixed solution; the mixed solution, a strong alkali solution, a surfactant and a complexing agent solution are simultaneously pumped into a stirred reactor in a continuous parallel flow reaction mode, the pH value of the reaction solution is controlled to be 10-13, the temperature in the reactor is 25-90°C, and an inert gas is passed during the reaction process; after the reaction is completed, the hydroxide containing Ni, Co and Mn is obtained through aging, filtration, washing and vacuum drying.

[0091] As an example, the preparation method of the positive electrode active material may include the following steps: mixing the positive electrode active material precursor with the Li source, sintering, and then post-processing (such as cooling, washing, and grinding) to obtain a ternary positive electrode active material.

[0092] The positive electrode active material precursor and the lithium source can be mixed by a ball mill mixer or a high-speed mixer. The mixed materials are added to an atmosphere sintering furnace for sintering. The sintering atmosphere is an oxygen-containing atmosphere, such as an air atmosphere or an oxygen atmosphere.

[0093] In the preparation of the positive electrode active material, the sintering process can be single constant temperature sintering or multiple sintering, or sintering with a temperature gradient change.

[0094] In some embodiments of the present invention, the Ni source includes at least one of nickel sulfate, nickel nitrate, nickel chloride, nickel oxalate or nickel acetate; and / or the Co source includes at least one of cobalt sulfate, cobalt nitrate, cobalt chloride, cobalt oxalate or cobalt acetate; and / or the Mn source includes at least one of manganese sulfate, manganese nitrate, manganese chloride, manganese oxalate or manganese acetate; and / or the Li source includes at least one of lithium oxide (Li2O), lithium phosphate (Li3PO4), lithium dihydrogen phosphate (LiH2PO4), lithium acetate (CH3COOLi), lithium hydroxide (LiOH), lithium carbonate (Li2CO3) or lithium nitrate (LiNO3).

[0095] In addition, the positive electrode active material can also be coated. Specifically, the coating material is coated on the surface of the positive electrode active material by dry coating (high temperature solid phase method), and the surface of the positive electrode active material is partially or completely coated with a coating layer formed by the coating material. The coating layer contains at least one element selected from the following (hereinafter referred to as "coating element"): aluminum (Al), titanium (Ti), tungsten (W), boron (B), phosphorus (P), cobalt (Co), yttrium (Y) and silicon (Si).

[0096] The positive electrode active material layer may further include a conductive agent and a binder in addition to the above-mentioned positive electrode active material.

[0097] The conductive agent is used to provide conductivity in the electrode. Any conductive agent can be used without particular limitation as long as it has suitable electronic conductivity and does not cause adverse chemical changes in the battery. Preferred are carbon materials such as carbon nanofibers, carbon blacks such as acetylene black and Ketjen black, activated carbon, graphite, mesoporous carbon, fullerenes, and carbon nanotubes.

[0098] The binder improves the adhesion between the positive electrode active material particles and the adhesion between the positive electrode active material and the current collector. Therefore, in the embodiment, the binder suitable for use is a fluorinated polyolefin binder, which may include but is not limited to polyvinylidene fluoride (PVDF), vinylidene fluoride copolymers or their modified (e.g., carboxylic acid, acrylic acid, acrylonitrile, etc.) derivatives.

[0099] The present invention has no particular limitation on the positive electrode current collector as long as it has conductivity and does not cause adverse chemical changes in the battery, and can use, for example: stainless steel, aluminum, nickel, titanium, fired carbon; or aluminum or stainless steel surface-treated with one of carbon, nickel, titanium, silver, etc.

[0100] In the present invention, the positive electrode sheet can be prepared according to conventional methods in the art. For example, the positive electrode active material, the conductive agent and the binder are dispersed in a solvent, and the solvent can be N-methylpyrrolidone (NMP) or deionized water to form a uniform positive electrode slurry, and the positive electrode slurry is coated on the positive electrode collector, and after drying, rolling and other processes, the positive electrode sheet is obtained.

[0101] As for the negative electrode plate, the negative electrode plate of the present invention includes a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector. The negative electrode active material layer includes a negative electrode active material and may further include a conductive agent and / or a binder.

[0102] The present invention places no particular limitation on the negative electrode current collector, as long as it has high electrical conductivity and does not cause adverse chemical changes in the battery. For example, copper, stainless steel, aluminum, nickel, titanium, fired carbon, copper or stainless steel surface-treated with one of carbon, nickel, titanium or silver, or an aluminum-cadmium alloy can be used.

[0103] Regarding the negative electrode active material, the embodiments of the present invention do not specifically limit the type of the negative electrode active material, and it can be selected according to actual needs. As an example, the negative electrode active material can be natural graphite, artificial graphite, mesocarbon microbeads (MCMB), hard carbon, soft carbon, silicon, silicon-carbon composite, SiOm (0 < m < 2, such as m = 1), Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO2, spinel-structured lithium titanate Li4Ti5O 12 、Li-Al alloy, and one or more of metallic lithium.

[0104] The embodiments of the present invention do not specifically limit the types of the conductive agent and the binder in the negative electrode active material layer, and they can be selected according to actual needs. As an example, the conductive agent is one or more of graphite, superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers; the binder is one or more of styrene-butadiene rubber, polyvinylidene fluoride, polytetrafluoroethylene, polyvinyl butyral, water-based acrylic resin, and carboxymethyl cellulose. The negative electrode active material layer may also optionally include a thickening agent, such as carboxymethyl cellulose.

[0105] Regarding the sulfur-containing additive, in one embodiment, the sulfur-containing additive includes at least one of sulfonate additives, sulfate additives, or sulfite additives.

[0106] In one embodiment, the sulfonate additives include at least one of methylene methanesulfonate (MMDS), ethyl ethane disulfonate, propyl methane disulfonate, 1,3-propane sultone (1,3-PS), 1-propene-1,3-sultone, or 1,4-butane sultone (1,4-BS).

[0107] In one embodiment, the sulfate additives include at least one of ethylene sulfate (DTD), propylene sulfate, 4-methyl ethylene sulfate (MDTD), 4-ethyl ethylene sulfate, 4-propyl ethylene sulfate, or propylene sulfate.

[0108] In one embodiment, the sulfite additives include at least one of ethylene sulfite (ES), dimethyl sulfite, or diethyl sulfite.

[0109] In the electrolyte, the sulfur-containing additive may be present in an amount of 0.1 to 2.5 wt. % based on the weight of the electrolyte.

[0110] As for the electrolyte, the electrolyte of the present invention includes, in addition to the sulfur-containing additive, an electrolyte and a solvent.

[0111] The electrolyte may typically include a lithium salt.

[0112] Specifically, the lithium salt includes at least one of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorobis(oxalatophosphate) (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP). The concentration of the electrolyte in the electrolyte may be 0.5 to 5 mol / L.

[0113] Specifically, the solvent includes at least one of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), cyclopentane (SF), dimethyl sulfone (MSM), methyl ethyl sulfone (EMS) and diethyl sulfone (ESE). Based on the weight of the electrolyte, the weight content of the solvent can be 70 to 98 wt.%.

[0114] In addition, the electrolyte may also include other additives. Specifically, the other additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high temperature performance, and additives that improve battery low temperature performance.

[0115] The secondary battery may also include a diaphragm, which is located between the positive electrode sheet and the negative electrode sheet, and is used to separate the positive electrode sheet and the negative electrode sheet to prevent the positive electrode sheet and the negative electrode sheet from contacting and short-circuiting. The diaphragm can be any material suitable for an electrochemical energy storage device isolation membrane in the art. Specifically, the diaphragm includes at least one of polyethylene, polypropylene, polyvinylidene fluoride, aramid, polyethylene terephthalate, polytetrafluoroethylene, polyacrylonitrile, polyimide, polyamide, polyester, and natural fiber.

[0116] Electronic Devices

[0117] An embodiment of the present invention provides an electronic device, comprising the secondary battery described above. The secondary battery serves as a power supply for the electronic device.

[0118] The electronic device refers to any device that can utilize electrical energy and convert it into mechanical energy, thermal energy, light energy or other one or more forms of energy, such as electric motors, electric heat engines, electric light sources, etc. Specifically, it may include but is not limited to mobile devices, electric vehicles, electric trains, ships and satellites, energy storage systems, etc. Mobile devices may be mobile phones, laptops, drones, sweeping robots, electronic cigarettes, etc.; electric vehicles may be pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.

[0119] The present invention is further described below with specific embodiments:

[0120] Example 1

[0121] Embodiment 1 provides a lithium ion battery, and the preparation method is as follows:

[0122] (1) Preparation of positive electrode sheet

[0123] (1.1) According to LiNi 0.9 Co 0.07 Mn 0.03 The molar ratio of each element Li, Ni, Co, and Mn in the chemical formula O2 is as follows: nickel sulfate, cobalt sulfate, manganese sulfate, and lithium hydroxide are weighed respectively, wherein lithium hydroxide is slightly excessive. Specifically, the ratio of the molar amount of lithium hydroxide to the total molar amount of nickel sulfate, cobalt sulfate, and manganese sulfate (Li / Me) is shown in Table 1;

[0124] (1.2) nickel sulfate, cobalt sulfate and manganese sulfate are dissolved in deionized water respectively, and each metal solution is transported to a reactor through a pipeline to form a mixed metal solution, and nitrogen is introduced as a protective gas, and an aqueous NaOH solution is added as a precipitant, urea is added as a surfactant, and ammonia water is added as a complexing agent to the mixed metal solution to obtain a mixed solution, and the pH of the mixed solution (i.e., the precursor reaction pH) is controlled to change gradually, and the reaction is carried out at 40° C., wherein the carbonyl concentration of the mixed solution (by controlling the amount of urea added), the precursor reaction pH and the reaction time are shown in Table 1; the product is filtered and dried at 110° C. to obtain a ternary precursor;

[0125] (1.3) The ternary precursor is mixed with lithium hydroxide and sintered. The sintering includes primary sintering and secondary sintering. The sintering atmosphere is an oxygen-containing atmosphere (the oxygen flow rate is 130m 3 / h), the temperature / time of the first sintering and the second sintering are shown in Table 1;

[0126] (1.4) Washing the sintered material, grinding and crushing it, and sieving it to obtain a ternary positive electrode active material;

[0127] (1.5) The positive electrode active material, binder (polyvinylidene fluoride), and conductive agent (carbon black) are mixed in a mass ratio of 97:1:2, and N-methylpyrrolidone (NMP) is added. The mixture is stirred in a vacuum mixer until the mixture becomes a positive electrode slurry with uniform fluidity; the positive electrode slurry is evenly coated on the positive electrode collector (12 μm thick aluminum foil); the positive electrode collector coated with the positive electrode slurry is transferred to an oven for drying, and then rolled and cut to obtain positive electrode sheets.

[0128] (2) Preparation of negative electrode sheet

[0129] The negative electrode active material (artificial graphite), conductive agent (CNT), thickener (carboxymethyl cellulose, CMC), and binder (styrene butadiene rubber, SBR) were mixed in a mass ratio of 96:2:1:1, and a negative electrode slurry was prepared by a wet process using a vacuum mixer. The negative electrode slurry was mixed at a single surface density of 86 g / m 2 The negative electrode current collector (6 μm thick copper foil) was evenly coated, and the negative electrode current collector coated with the negative electrode slurry was transferred to an oven for drying, and then rolled and cut to obtain a negative electrode sheet.

[0130] (3) Preparation of electrolyte

[0131] Ethylene carbonate (EC) and ethyl methyl carbonate (EMC) are mixed in a weight ratio of 1:1 to obtain an organic solvent, and then a sulfur-containing additive and lithium salt LiPF6 are dissolved in the mixed organic solvent. The concentration of LiPF6 is 1 mol / L. The type and addition amount of the sulfur-containing additive are shown in Table 1.

[0132] (4) Preparation of diaphragm

[0133] It adopts PP (polypropylene) / PE (polyethylene) / PP three-layer composite diaphragm.

[0134] (5) Preparation of batteries

[0135] The positive electrode sheet, separator and negative electrode sheet prepared above are wound to obtain a bare cell without liquid injection; the bare cell is placed in an outer packaging foil, and the prepared electrolyte is injected into the dried bare cell, and a lithium-ion battery is obtained through vacuum packaging, standing, forming, shaping, sorting and other processes;

[0136] The standing and forming process is as follows: after the battery is filled and packaged, it is stood at 45°C for 2 hours, and then put on the machine for forming, charged to 2.4V at 0.02C, and then discharged to 2V. After 2 cycles of charge and discharge, it is charged to 3.4V at 0.02C, and then charged to 3.75V at 0.05C, and then taken off the machine, and the forming is completed.

[0137] Examples 2 to 14, Example 16, Comparative Examples 1 to 4

[0138] Examples 2 to 16 and Comparative Examples 1 to 4 respectively provide a lithium ion battery, and the preparation method is similar to that of Example 1, except that the Li / Me, carbonyl concentration, precursor reaction pH and time, primary sintering and secondary sintering temperature and time, and the type and addition amount of the sulfur-containing additive are shown in Table 1.

[0139] Embodiment 15

[0140] Example 15 provides a lithium ion battery, the preparation method is similar to that of Example 1, except that Li / Me, precursor reaction pH and time, primary sintering and secondary sintering temperature and time, and the type and addition amount of the sulfur-containing additive are shown in Table 1;

[0141] In the preparation method (1.2), no urea is added;

[0142] In the preparation method (1.4), the ground and crushed material is screened in large quantities to obtain H 50 The ternary positive electrode active material meets the requirements shown in Table 2.

[0143] Embodiment 17, 18

[0144] Embodiments 17 and 18 provide a lithium ion battery respectively, and the preparation method is similar to that of embodiment 1, except that:

[0145] Example 17 In the preparation method (1.1) step, according to LiNi 0.8 Co 0.12 Mn 0.08O2 chemical formula to weigh each material, Example 18 in the preparation method (1.1) step according to LiNi 0.7 Co 0.15 Mn 0.15 O2 chemical formula to weigh each material;

[0146] In addition, in Examples 17 and 18, Li / Me, carbonyl concentration, precursor reaction pH and time, primary sintering and secondary sintering temperature and time, and the type and addition amount of the sulfur-containing additive are shown in Table 1.

[0147] Table 1

[0148]

[0149]

[0150] For each embodiment and comparative example, the aspect ratio (H 50 ), the particle size change ratio of the positive electrode active material (△D 50 ), sulfur content in the negative electrode sheet (M S ), the detection is shown in Table 2, and the detection methods of the above items are as follows:

[0151] H 50 : Disassemble the lithium-ion battery to obtain the positive electrode sheet, soak the positive electrode sheet in DMC (dimethyl carbonate) at room temperature for 60 minutes, take it out, and dry it at room temperature with a humidity of ≤15%; scrape the positive electrode active material layer on the surface of the current collector, calcine it at 450°C for 3 hours to remove the conductive agent, binder, surface side reaction products, and residual electrolyte, and wash and dry it to obtain the positive electrode active material;

[0152] The positive electrode active material (3 g) was placed in a clean agate mortar, manually ground with a pestle for 5 min, passed through a 100-mesh sieve, and subjected to SEM testing; the nano measurer software was used to observe the 2.5K magnification particle morphology and measure the ratio of the major axis length to the minor axis length of the primary particles of the positive electrode active material; the number of samples collected was 200, and the aspect ratio corresponding to the cumulative distribution percentage of 50% was H. 50 .

[0153] △D 50 : Disassemble the lithium-ion battery to obtain the positive electrode sheet, soak the positive electrode sheet in DMC (dimethyl carbonate) at room temperature for 60 minutes, take it out, and dry it at room temperature with a humidity of ≤15%; scrape the positive electrode active material layer on the surface of the current collector, calcine it at 450°C for 3 hours to remove the conductive agent, binder, surface side reaction products, and residual electrolyte, and obtain the positive electrode active material through post-treatment;

[0154] The positive electrode active material was dispersed in an aqueous solution containing 3% sodium hexametaphosphate dispersant, and after continuous stirring with a glass rod for 10 circles, all the samples were quickly poured into the particle size distribution instrument test sample pool for D V 50 tests, get D before pressure maintenance V 50, denoted as D V 50 压前 ;

[0155] Then, the mixture containing the positive electrode active material is subjected to solid-liquid separation and drying to obtain the positive electrode active material again, and the positive electrode active material is pressed at a pressure of 35KN for 30s using a powder compactor; after the pressure is maintained, the positive electrode active material is taken out and D is measured again using a particle size tester according to the above method. V 50 test, get D after pressure maintenance V 50, denoted as D V 50 压后 ;

[0156] The particle size change ratio (△D 50 ):

[0157] △D 50 =|(D V 50 压前 -D V 50 压后 )| / D V 50 压前 ;

[0158] Among them, D V 50 is the particle size corresponding to when the cumulative volume distribution percentage of the positive electrode active material reaches 50%, in μm.

[0159] M S : Disassemble the lithium-ion battery to obtain the negative electrode sheet, soak the negative electrode sheet in DMC (dimethyl carbonate) at room temperature for 12 hours, take it out, replace it with new DMC and soak the negative electrode sheet again for cleaning, and repeat the cleaning several times until the sulfur content detected in the DMC solution is less than 10ppm;

[0160] The cleaned negative electrode sheet was taken out and ICP test was performed. The specific test conditions were as follows: scrape off the negative electrode active material layer on the surface of the negative electrode current collector, weigh 0.5g of the sample and dissolve it in 20ml of water, then add 10ml of nitric acid, heat to dissolve, dilute with water, and finally filter to obtain the test solution; pipette 10ml of the test solution and continue to add 5ml of hydrochloric acid and continue to dilute with water to 100ml; the obtained solution was calibrated and tested with iCAP PRO XP inductively coupled plasma emission spectrometer, according to the standard curve method, horizontal observation angle, constant temperature 25°C; M S .

[0161] Table 2

[0162] <![CDATA[H 50 ]]> <![CDATA[△D 50 ]]> <![CDATA[M S (ppm)]]> a×Ln(b) Example 1 1.495 0.68 98 11.08 Example 2 1.321 0.82 112 10.03 Example 3 1.530 0.64 160 12.54 Example 4 1.512 0.78 177 13.26 Example 5 1.358 0.61 82 8.82 Example 6 1.587 0.73 75 11.74 Example 7 1.241 0.85 139 9.75 Example 8 1.386 0.53 192 10.46 Example 9 1.324 0.60 88 8.56 Example 10 1.527 0.81 179 13.66 Embodiment 11 1.211 0.51 107 7.35 Example 12 1.584 0.84 183 14.70 Example 13 1.513 0.89 195 14.10 Embodiment 14 1.286 0.55 72 7.59 Embodiment 15 1.184 0.47 159 7.49 Example 16 1.482 0.92 221 14.16 Embodiment 17 1.352 0.79 164 11.05 Embodiment 18 1.426 0.66 95 10.10 Comparative Example 1 1.223 0.51 70 6.79 Comparative Example 2 1.594 0.90 196 15.36 Comparative Example 3 1.354 0.87 5 3.62 Comparative Example 4 1.056 0.56 114 6.27

[0163] The performance of the lithium-ion batteries prepared in the above embodiments and comparative examples was tested. The specific items and methods are as follows. The results are shown in Table 3.

[0164] (1) High and low temperature interval cycle capacity retention rate:

[0165] First calculate the initial capacity:

[0166] The lithium-ion battery is placed in a 25°C environment and left to stand until the lithium-ion battery reaches a constant temperature; at 25°C, it is charged to 4.3V at a constant current of 0.33C and charged to 0.05C at a constant voltage; it is discharged to 2.75V at 0.33C, and this capacity is taken as the initial capacity, recorded as C0;

[0167] Then perform high and low temperature interval cycle:

[0168] Place the lithium-ion battery in a 5°C environment and let it stand for 4 hours; at 5°C, charge it at a constant current of 0.33C to 4.3V, charge it at a constant voltage to a current of 0.05C; discharge it at 0.33C to 2.75V, and repeat this step 10 times;

[0169] Then place the lithium-ion battery in a 45°C environment and let it stand for 4 hours; at 45°C, charge it at a constant current of 0.33C to 4.3V, charge it at a constant voltage to a current of 0.05C; discharge it at 0.33C to 2.75V, and repeat this step 10 times;

[0170] This is a high and low temperature cycle unit. According to this step, a total of 10 high and low temperature cycle units are charged and discharged;

[0171] Record the capacity of the last cycle in the 10th high and low temperature cycle unit, recorded as C1;

[0172] Calculate the high and low temperature interval cycle capacity retention rate = C1 / C0×100%.

[0173] (2) Self-discharge performance:

[0174] Place the lithium-ion battery in a 25°C environment, charge it to 3.85V at a constant current of 0.5C, then charge it to 0.05C at a constant voltage of 3.85V, leave it in a 25°C±3°C environment for two days, test and record the voltage OCV1 (in mV) at this time;

[0175] Then, the lithium-ion battery is placed in an environment of 45°C ± 3°C for 10 days and in an environment of 25°C ± 3°C for two days, and the voltage OCV2 (in mV) is tested and recorded.

[0176] The K value was obtained by the following formula: K (mV / h) = (OCV2 - OCV1) / (10 x 24h).

[0177] Table 3

[0178]

[0179]

[0180] For the lithium-ion batteries prepared in the embodiments of the present invention, after high and low temperature interval cycles, the capacity retention rate is ≥75%, and the battery has good cycle stability; the voltage drop rate is low under high temperature conditions, and the self-discharge condition is improved.

[0181] According to the test results of Comparative Examples 1 to 4, when the value of a×Ln(b) of the lithium-ion battery exceeds the range of 7.3 to 14.8, the lithium-ion battery cannot achieve good high and low temperature interval cycle stability, and the self-discharge situation is more serious.

[0182] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A secondary battery, comprising a positive electrode sheet, a negative electrode sheet and an electrolyte; the positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, the positive electrode active material layer comprising a positive electrode active material; characterized in that: The electrolyte includes a sulfur-containing additive; The secondary battery satisfies the following relationship: a=(H 50 ) 2 -(1 / 3)H 50 +△D 50 ,b=M S ,7.3≤a×Ln(b)≤14.8; Among them, H 50 The aspect ratio corresponding to the cumulative distribution percentage of the primary particles of the positive electrode active material reaching 50%; △D 50 D is the positive electrode active material under 35KN pressure for 30s before and after V 50 particle size change ratio; M S It is the mass content of sulfur element in the negative electrode plate, in ppm.

2. The secondary battery according to claim 1, characterized in that: The secondary battery satisfies the following relationship: 8.8≤a×Ln(b)≤13.

3.

3. The secondary battery according to claim 1, characterized in that: The sulfur-containing additive includes at least one of a sulfonate additive, a sulfate additive or a sulfite additive.

4. The secondary battery according to claim 3, characterized in that: The sulfonate additive includes at least one of methylene methanedisulfonate, ethylene ethanedisulfonate, propylene methanedisulfonate, 1,3-propane sultone, 1-propylene-1,3-sultone or 1,4-butane sultone; and / or, The sulfate ester additive includes at least one of vinyl sulfate, 4-methylethylene sulfate, 4-ethylethylene sulfate, 4-propylethylene sulfate or propylene sulfate; and / or, The sulfite additive includes at least one of vinyl sulfite, dimethyl sulfite or diethyl sulfite.

5. The secondary battery according to claim 1, characterized in that: The H 50 The range is 1.2 to 1.

6.

6. The secondary battery according to claim 5, characterized in that: The H 50 The range is 1.32~1.

53.

7. The secondary battery according to claim 1, characterized in that: The ΔD 50 The range is 0.50~0.

90.

8. The secondary battery according to claim 7, characterized in that: The ΔD 50 The range is 0.60~0.

82.

9. The secondary battery according to claim 1, characterized in that: The M S The range is 70~200ppm.

10. The secondary battery according to claim 9, characterized in that: The M S The range is 80~180ppm.

11. The secondary battery according to claim 1, characterized in that: The positive electrode active material includes a ternary positive electrode material, the chemical formula of which is LiNi x Co y Mn (1-x-y) O2, where 0.7≤x<1, 0<y≤0.3, 0<x+y<1.

12. An electronic device, characterized in that: A secondary battery comprising the secondary battery according to any one of claims 1 to 11.